2021
DOI: 10.1186/s12986-021-00569-w
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 phosphorylation in central leptin resistance

Abstract: Mechanism exploitation of energy homeostasis is urgently required because of the worldwide prevailing of obesity-related metabolic disorders in human being. Although it is well known that leptin plays a central role in regulating energy balance by suppressing food intake and promoting energy expenditure, the existence of leptin resistance in majority of obese individuals hampers the utilization of leptin therapy against these disorders. However, the mechanism of leptin resistance is largely unknown in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 146 publications
(77 reference statements)
1
53
0
Order By: Relevance
“…It has been reported that selective ablation of JNK1 from the mouse central nervous system (CNS) significantly reduces HFD-induced obesity [128,129]. Similarly, other signaling pathways, such as the Janus kinase 2 (JAK2)/signal transducer and activator of transcription-3 (STAT3) [130,131], forkhead box protein O1 (FOXO1) [132,133], and mechanistic target of rapamycin (mTOR) [134][135][136][137] might get dysregulated by inflammatory insults in the hypothalamus during obesity. This leads to an increase in the protein-tyrosine phosphatase 1B (PTP1B) and suppressor of cytokine signaling 3 (SOCS3) levels through the activation of IKKβ/NF-κB, thereby eventually causing aberrant energy balance and obesity [20,138].…”
Section: Metabolic Disorders Aging and Hypothalamic Inflammation A Obesity And Hypothalamic Inflammationmentioning
confidence: 99%
“…It has been reported that selective ablation of JNK1 from the mouse central nervous system (CNS) significantly reduces HFD-induced obesity [128,129]. Similarly, other signaling pathways, such as the Janus kinase 2 (JAK2)/signal transducer and activator of transcription-3 (STAT3) [130,131], forkhead box protein O1 (FOXO1) [132,133], and mechanistic target of rapamycin (mTOR) [134][135][136][137] might get dysregulated by inflammatory insults in the hypothalamus during obesity. This leads to an increase in the protein-tyrosine phosphatase 1B (PTP1B) and suppressor of cytokine signaling 3 (SOCS3) levels through the activation of IKKβ/NF-κB, thereby eventually causing aberrant energy balance and obesity [20,138].…”
Section: Metabolic Disorders Aging and Hypothalamic Inflammation A Obesity And Hypothalamic Inflammationmentioning
confidence: 99%
“…After recruitment by JAK2, STAT3 dimerizes and translocates to the nucleus after Tyr705 phosphorylation. The activation of STAT3 signaling can induce changes in the expression of downstream molecules and regulate biological processes such as cell migration, proliferation, and apoptosis [20]. Previous studies have shown that the JAK2/STAT3 pathway is involved in the progression of colorectal cancer [18] and central nervous system diseases related to experimental cerebral ischemia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin resistance is characterized by decreased satiety, excessive food consumption, and an increase in total body mass [ 33 ] and a significant issue in obesity. While controversial, enhanced STAT3 activation is regarded to ameliorate leptin resistance [ 34 ]. Indeed, STAT3 activity was considerably increased in the hypothalamus of diet-induced obesity mice, accompanied by lower pro-opiomelanocortin (POMC) expression and abnormal metabolic physiological behaviors, implying that increased STAT3 activity negatively affected leptin-mediated POMC expression in diet-induced obesity mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While controversial, enhanced STAT3 activation is regarded to ameliorate leptin resistance [ 34 ]. Indeed, STAT3 activity was considerably increased in the hypothalamus of diet-induced obesity mice, accompanied by lower pro-opiomelanocortin (POMC) expression and abnormal metabolic physiological behaviors, implying that increased STAT3 activity negatively affected leptin-mediated POMC expression in diet-induced obesity mice [ 34 ]. Moreover, excess STAT3 activity inhibited POMC expression in the hypothalamus of diet-induced obesity mice, implying that STAT3 inhibition may promote leptin signaling [ 35 ].…”
Section: Discussionmentioning
confidence: 99%